2021
DOI: 10.3390/su13010390
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Climate and Extreme Weather on Fatal Traffic Accidents

Abstract: Climate change and the extreme weather have a negative impact on road traffic safety, resulting in severe road traffic accidents. In this study, a negative binomial model and a log-change model are proposed to analyse the impact of various factors on fatal traffic accidents. The dataset used in this study includes the fatal traffic accident frequency, social development indicators and climate indicators in California and Arizona. The results show that both models can provide accurate fitting results. Climate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Motor vehicle crash injuries were estimated to be the ninth leading cause of death worldwide in 2004 and are predicted to rise to the fifth leading cause by 2030 (3). The risk of FVCs in all drivers is attributable to a variety of factors, including human factors (e.g., male sex, age [novice or elderly driver], low educational level, physical diseases, alcohol use, illicit or prescription drug use, excessive speeding, distracted driving, driver fatigue, and careless driving), equipment factors (e.g., unsafe vehicle design and air bags), environmental factors (e.g., adverse weather, rural or wet roads, poor lighting, and unsafe road infrastructure), enforcement (e.g., seatbelt use, cell phone use while driving, previous history, of traffic offenses or involvement in motor vehicle crashes, swerving, inadequate traffic laws, and poor law enforcement powers), and medical response (e.g., slow emergency medical response time in remote areas) (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Motor vehicle crash injuries were estimated to be the ninth leading cause of death worldwide in 2004 and are predicted to rise to the fifth leading cause by 2030 (3). The risk of FVCs in all drivers is attributable to a variety of factors, including human factors (e.g., male sex, age [novice or elderly driver], low educational level, physical diseases, alcohol use, illicit or prescription drug use, excessive speeding, distracted driving, driver fatigue, and careless driving), equipment factors (e.g., unsafe vehicle design and air bags), environmental factors (e.g., adverse weather, rural or wet roads, poor lighting, and unsafe road infrastructure), enforcement (e.g., seatbelt use, cell phone use while driving, previous history, of traffic offenses or involvement in motor vehicle crashes, swerving, inadequate traffic laws, and poor law enforcement powers), and medical response (e.g., slow emergency medical response time in remote areas) (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…A high volumeto-capacity ratio results in congestion, i.e., an increase in travel time, which brings with it a number of indirect effects, such as increased air pollution, noise, and vehicle operating costs [8]. In addition, studies have shown that adverse weather conditions significantly affect the probability of accidents [9].…”
Section: Introductionmentioning
confidence: 99%
“…Each road traffic incident has its own set of, generally preventable, drivers impacts in terms of fatalities and injuries and primary causes such as excess speed, overloading, and types of vehicles [9]. Moreover, climate change and extreme weather are leading to changing risks for severe road traffic accidents and injuries [10], as well as spatial, temporal, and community aspects [11]. Finally, the number of cars per day, crosswalks, road types, highway speed limits, and the real-time post-impact traffic accident management system should be taken into account [12,13].…”
Section: Introductionmentioning
confidence: 99%